The association of the ALBI score with disease severity and perinatal outcomes in the preeclampsia spectrum - Akcabay, Cigdem; Onat, Miray; Aslan, Neslihan; Kavak, Ebru Celik; Sanli, Cengiz; Batmaz, Ibrahim; Kavak, Salih Burcin (Bmc, 2026)
Background This study aimed to investigate the association between the albumin-bilirubin (ALBI) score and disease severity across the preeclampsia spectrum and to evaluate its relationship with perinatal outcomes, with particular emphasis on differences according to gestational age. Methods In this retrospective cross-sectional study, medical records of 370 pregnant women diagnosed with preeclampsia between June 2021 and June 2025 were analyzed. Patients were stratified by gestational age at delivery (< 34 weeks and >= 34 weeks) and by disease severity (mild-to-moderate preeclampsia vs. severe preeclampsia). Maternal biochemical, hematological, and inflammatory parameters were recorded, and the ALBI score was calculated using serum albumin and total bilirubin levels. Perinatal outcomes included birth weight, Apgar scores, umbilical cord blood gas parameters, admission to the Neonatal Intensive Care Unit (NICU), and length of NICU stay. Receiver operating characteristic analyses were performed to assess the discriminative performance of the ALBI score. Results The ALBI score was significantly higher in severe preeclampsia regardless of gestational age and showed superior discriminative performance compared with inflammatory indices, particularly in early-onset disease (< 34 weeks; AUC = 0.702). Higher ALBI scores were associated with adverse perinatal outcomes, including lower birth weight and increased NICU admission. In contrast, inflammatory indices (NLR, PLR, LMR, and SII) did not demonstrate clinically meaningful discrimination of disease severity or neonatal risk. Gestational age at delivery was the primary determinant of NICU length of stay. Conclusions The ALBI score is a robust, low-cost, and easily applicable biomarker that reflects biochemical disease severity and perinatal risk across the preeclampsia spectrum, particularly in early-onset severe preeclampsia. Prospective multicenter studies are required to confirm its clinical utility and define its role in future risk stratification algorithms.
Keywords: Preeclampsia; Albi Score; Disease Severity; Gestational Age; Perinatal Outcomes